Detection of Patotypes of Escherichia coli Strains Causing Childhood Diarrhea in Health Establishments of the Lambayeque-Peru Region, 2018 - Yacarini-Martínez, Antero Enrique (2020)
Objetive. To identify pathotypes of virulence genes of Escherichia coli from diarrheal samples of children under five years of age in the Lambayeque Region, in the period April-September 2018. The study: Descriptive and cross-sectional study. 75 E. coli strains from diarrheogenic samples were analyzed using real-time Multiplex PCR and primers for E. coli pathotype genes: daaD, aggR, eaeA, stx, ipaH and st. Findings: 34.66% (26/75) of virulence genes were detected from the total isolates. The enterotoxigenic E. coli pathotype presented the highest frequency, 18.67% (14/75) of the total isolates. It was also detected that the enterotoxigenic E. coli pathotype appeared in 53.86% (14/26) of the total positive strains. Also, in 11.54% of positive strains (3/26) they presented more than one pathotype. Conclusion: Molecular epidemiology will help a better, adequate and timely diagnosis of childhood diarrhea in this vulnerable population.